2016
DOI: 10.1016/j.yjmcc.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of myocardial fatty acid oxidation prevents diastolic dysfunction in mice subjected to angiotensin II infusion

Abstract: Rationale Diastolic dysfunction is a common feature in many heart failure patients with preserved ejection fraction and has been associated with altered myocardial metabolism in hypertensive and diabetic patients. Therefore, metabolic interventions to improve diastolic function are warranted. In mice with a germline cardiac-specific deletion of acetyl CoA carboxylase 2 (ACC2), systolic dysfunction induced by pressure-overload was prevented by maintaining cardiac fatty acid oxidation (FAO). However, it has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 50 publications
(54 reference statements)
2
46
0
Order By: Relevance
“…As reported before, mice challenged with Ang II develop heart fibrosis (Choi et al, 2016). Crenolanib treatment significantly reduced heart fibrosis as determined by picrosirius red-positive area per total area (Figure 6a and b).…”
Section: Resultsmentioning
confidence: 68%
“…As reported before, mice challenged with Ang II develop heart fibrosis (Choi et al, 2016). Crenolanib treatment significantly reduced heart fibrosis as determined by picrosirius red-positive area per total area (Figure 6a and b).…”
Section: Resultsmentioning
confidence: 68%
“…Furthermore, increased activity of this enzyme, which is involved in the reaction of hypoxanthine and xanthine to UA, causes the release of free radicals and increased oxidative stress. Oxidative stress also contributes to the pathogenesis of HFpEF . Several studies have previously examined whether UA‐lowering therapy with xanthine oxidase inhibitor allopurinol or oxypurinol leads to clinical and functional improvement of HF; however, the results are not consistent .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also contributes to the pathogenesis of HFpEF. 24,25 Several studies have previously examined whether UA-lowering therapy with xanthine oxidase inhibitor allopurinol or oxypurinol leads to clinical and functional improvement of HF; however, the results are not consistent. [26][27][28][29][30] Cingolani and colleagues 26 indicated that inhibition of xanthine oxidase by oxypurinol in patients with chronic HF decreased UA level and improved LVEF in patients with LVEF ≤40% after 1 month of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…M-mode image sequences and Tissue Doppler imaging (TDI) was performed on the Vevo 2100 High-Resolution Imaging System (VisualSonics, Toronto, Ontario, Canada) with a MS400 MicroScan Transducer, centered at 30 MHz [13, 14]. …”
Section: Methodsmentioning
confidence: 99%